Genomic and phylogenetic characterization of Merino Walk virus, a novel arenavirus isolated in South Africa - Palacios, Gustavo (Society for General Microbiology, 2010)
Merino Walk virus (MWV), a proposed novel tentative species of the family Arenaviridae, was isolated from a rodent, Myotomys unisulcatus, collected at Merino Walk, Eastern Cape, South Africa, in 1985. Full-length genomic sequence confirmed MWV as an arenavirus related distantly to Mobala, Mopeia and Ippy viruses, all members of the Old World arenavirus complex. We propose MWV as a tentative novel species in the Lassa–lymphocytic choriomeningitis virus complex, based on its isolation from a novel rodent species and its genetic and serological characteristics.